Influence of code of points in training systematization of mens artistic gymnastics - Paulo D.S. Carrara (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to determine the influence of the 2006 Code of Points (CP) on the systematization of high level men's artistic gymnastics training. To understand these alterations, eight senior coaches of national teams - Portugal and Brazil - were questioned about the changes in the CP rules and their respective influence on training. For the interviews, a comparative analysis between the rules of the 2001 and 2006 CP was performed, whose results were used to construct and validate the questionnaires.Two questionnaires of 12 items each, as well as four complementary questions, were answered and commented upon. Descriptive (mean and standard deviation) and inferential (Mann-Whitney test) statistics was used for analysis of the items. Content analysis was used for evaluation of the comments. No significant differences were observedbetween the answers to the items of the two questionnaires given by the coaches of either country. However, regarding comments, the coaches expressed some tendencies toward training changes. In this respect, an increase in training volume and intensity was introduced into Physical Preparation; in Technical Preparation a wider element variety and element difficulty of the different groups were necessary; in Tactical Preparation routines involving a larger number of more difficult elements, including dismount, wereobserved. The main results permit to conclude that the 2006 CP led to changes in routine composition, with the use of a more varied number of elements on the apparatuses. Gymnast performances on the different apparatuses is not only conditioned by trainingcharacteristics, but also by the gymnast's individual potential, inferring that the process of technical development of the gymnast should be more diversified.